Emotional Labor in Raudhatul Athfal (RA) Teachers’ Multi-Role Work: Initial Findings - Fanny Rizkiyani; Syifa Mufiedatussalam (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Emotional labor among teachers in Raudhatul Athfal (RA), Islamic early childhood education in Indonesia, is a complex and underexplored phenomenon. This study aims to explore and provide preliminary findings of the emotional labor experiences of RA teachers. Using a qualitative case study design, ten female RA teachers from Bandung, Indonesia, were recruited through convenience sampling. This study utilized an open-ended online survey and Braun and Clarke’s reflexive thematic analysis as data collection method and analysis, respectively. Three themes emerged. The first theme is Multirole Job Demands, with sub-themes: RA teachers’ job characteristics (n=10), multirole demands (n=8), cultural display rules (n=5), and spiritual educators as emotional labor intensifier (n=4). The second theme is Emotional Labor Strategies, with sub-themes: surface acting (n=6), and deep acting (n=3). The last theme is Islamic Framework in Emotional Labor, with sub-themes: Islamic practices as emotional regulation resources and strategies (n=6), spiritual meaning-making (n=9), and workplace spirituality (n=2). The overall emotional labor experiences of the RA teachers are discussed. The findings highlight key constructs that can be explored and directly measured in future research to validate the emotional labor process among RA teachers in Indonesia. Ultimately, this research can contribute to developing support programs for RA teachers that effectively promote their well-being. Keywords: surface acting, deep acting, early childhood teachers, spirituality, Islamic education